Desa Mawacara, Negara Mawatata: Bali’s Customary Village-Based State Policies in the Time of the Covid-19 Pandemic - Suryawan, I Ngurah (Jurnal Politik, 2020)
Balinese customary villages are at the center of the state’s strategy for mitigation of Covid-19. Relations between customary villages and the state predate colonial times. The historical dynamics have shown that the traditions and cultures of customary villages (desa mawacara) will always exist within the shadow of the state (negara mawatata). The symbolic narrative of desa mawacara, negara mawatata illustrates the governmentality that the state exercises over the villages. Regional Regulation No. 4/2019 on Customary Villages in Bali and the formation of the customary village-based task force were rational choices made by the Governor of Bali to place the villages at the forefront of the province’s strategy against the pandemic. This article employs Li’s (2012) adaptation of Foucault’s concept of governmentality in its analysis. Discourse analysis was conducted with regards to information extracted from mass media, indepth interviews, and participatory observation. This article argues that the state’s policies for Balinese customary villages are deeply entrenched in its long history of intervention and cooptation. During the Covid-19 pandemic, the state has been well aware of the extensive influence that customary villages hold over their communities. The state utilizes this reality to exert its authority.